Age and genetic determinants of variation of circulating levels of the receptor for advanced glycation end products (RAGE) in the general human population. (January 2015) - Prakash, Jai; Pichchadze, Guram; Trofimov, Svetlana; Livshits, Gregory
Highlights: Contribution of age, body composition and genetics on sRAGE variation was assessed. The statistically significant correlation of sRAGE with fat free mass was discovered. Genetics explained ∼30% of sRAGE variation and was involved in correlation with body composition. We observed highly significant and previously not reported correlation with fat free mass. Abstract: In stark contrast to many other blood biomarkers, including a variety of inflammatory cytokines, the main factors affecting sRAGE variation in the general human population are virtually unknown. We examined the contribution of age, body composition, and putative genetic sources to the interindividual variation of sRAGE. Its plasma levels were measured in 1557 apparently healthy individuals from 359 nuclear families. Statistical analysis revealed that all the aforementioned factors are statistically significantly associated with sRAGE levels. The levels of sRAGE consistently decreased with age ( R  = −0.264, p  = <0.001) and with the indices of obesity, such as BMI. However, of special interest was the highly significant and previously not reported independent correlation with fat free mass ( p  < 0.001). The putative genetic effects explained 0.291 ± 0.089 of sRAGE variation and were solely responsible for the phenotypic correlations with the obesity phenotypes (genetic correlations, −0.22 ± 0.09 and −0.33 ± 0.09). Taken together, these data suggest that although genetically determined to a substantial degree, the sRAGE levels also depend on age and obesity, which in turn, increase the risk for a variety of pathological conditions associated with sRAGE. Clearly, identifying the metabolic pathways and specific genetic factors is the next important stage in this research area.